Effects of information loss in texture details due to the PIFS encoding on load and friction in hydrodynamic bearings - Wolski, Marcin; Podsiadlo, Pawel; Stachowiak, Gwidon (Pergamon, 2011)
Textured surfaces can significantly improve the performance of hydrodynamic bearings. However, there is no generally accepted method for their accurate and automated 3D characterization. A promising solution to this problem is partition iterated function system (PIFS) model, which encapsulates information about 3D topography of textured surfaces. However, some loss in surface details can occur. Therefore, before PIFS could be used, effects of this information loss on load and friction need to be investigated. In this study, this issue was addressed using a textured hydrodynamic pad bearing. The results obtained showed that PIFS models might become useful in characterization of textured surfaces.